Basic electronics for scientists - Brophy, James J. (New York : McGraw Hill Education, 1990)
Aims to provide science and engineering students with a basic knowledge of electronics and electonic devices and circuits, ranging from DC circuits to digital circuits and microprocessors. The text is designed for courses in electrical instrumentation and measurements, and solid state electronics.
Direct Current Circuits -- Alternating Currents -- Diode Circuits -- Semiconductor Devices -- AC-Circuit Analysis -- Transistor Amplifiers -- Operational Amplifiers -- Oscillators -- Digital Electronics -- Analog and Digital Measurements -- Microprocessors -- Microprocessor Circuits
Includes bibliographical references and index.
Keywords: ELECTRONICS